Photocatalytic Degradation of Reactive Dyes Using the Novel Hexagonal Magnetic Titanium Dioxide Composites - Shen, Yong-Miao; Zhi, Duo; Wang, Wei; Tao, Fei-Fei (Asian Journal of Chemistry, 2011)
The novel magnetic photocatalysts, TiO2/Fe3O4 and TiO2/SiO2/Fe3O4 composites were prepared for degradation of reactive dyes. The photoactive TiO2 was deposited onto the magneticFe3O4or SiO2/Fe3O4 cores by using a sol-gel coating technique. The morphologies and structures of the photocatalysts were characterized by transmission electron microscopy and X-ray diffraction. The photocatalytic activities of TiO2/Fe3O4 under UV light irradation were investigated by studying the effects of the initial pH values of the solutions and irradiation times on the degradation rates of various of reactive dyes. Compared with TiO2, the TiO2/Fe3O4 and TiO2/SiO2/Fe3O4 composites expressed excellent photocatalytic activities for various reactive dyes. The recycling experimental results showed that TiO2/SiO2/Fe3O4 was a highly effective decolouring agent and could effectively be seperated from wastewater under the external magnetic field. After being recycled many times, the novel photocatalyst could hold on the degradation rate of 85 % on reactive brilliant blue.